The discursive structure of denunciation in the story "Agua" by José María Arguedas - Navarrete Salazar, Manuel Alfonso (2021)
The Linguistics of the text proposes the study of a text from a global point of view, since it conceives it as a coherent unit, carrying meaning. From the perspective of that field of study, this research aims to show how, in the story "Agua" by José María Arguedas, there is an underlying textual superstructure corresponding to a discourse of denunciation, which becomes evident in the elements that form part of the fictional universe proposed by the story. We make use of the discursive categories that the researcher María Claudeville postulated as recurring in the textual structures of the denunciation discourses. These categories are present in the possible world manifested in the story "Agua", in which the existence of a problem and the search for a solution are exposed. Thus, it is shown how a fictitious text can serve as a means to publicize a speech of denunciation.